Basic Skills of Straight Kicks for Pencak Silat Athletes of PPLP South Sulawesi - Asyhari, Hasbi; Nurliani, Nurliani (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objectives. The fundamental movements of pencak silat are characterized by coordination, planning, direction, and control. Proficiency in fundamental techniques is essential, as technique is a crucial component in every sequence of martial arts motions. This study seeks to assess the proficiency of fundamental straight kick techniques among PPLP South Sulawesi pencak silat athletes. Materials and Methods. The research methodology employed is quantitative descriptive. The methodology employed in the study This is a survey method utilizing data collection techniques to assess Pencak Silat skill performance. Study Population These are all 12 pencak silat athletes from PPLP South Sulawesi. The sampling technique employed is Purposive Sampling, resulting in a sample size of six male participants. The instrument utilized in this study is the pencak silat skills performance test. Results. Utilize descriptive quantitative analysis for data examination. Which was expressed as a percentage. The percentage of South Sulawesi PPLP pencak silat athletes' proficiency in basic straight kick skills using the right foot is categorized as follows: "Very Good" at 100% (6 athletes), "Good" at 0% (0 athletes), "Enough" at 0% (0 athletes), "Less" at 0% (0 athletes), and "Very Less" at 0% (0 athletes). The fundamental straight kick proficiency of PPLP South Sulawesi pencak silat athletes utilizing the left foot is classified as "Very Good" at 66.67% (4 athletes), "Good" at 33.33% (2 athletes), with no athletes in the "Enough," "Less," or "Very Less" categories, each at 0% (0 athletes). The analysis indicates that the basic straight kick proficiency of the PPLP South Sulawesi pencak silat athletes utilizing their dominant left foot is classified as Very Good. Conclusion. The analysis indicates that the basic straight kick talents of the PPLP South Sulawesi pencak silat competitors are primarily classified in the Very Good group.